Consumo alimentario y su relación con obesidad en adultos de 40 a 55 años del Sector ‘’Barrio Sur’’ del cantón Jujan, provincia del Guayas diciembre 2022 - mayo 2023. - Bowen Escobar, Génesis Dayana (2023)
Knowing what about people's food consumption is important because it will help us to know what types of food influence people's nutritional status. This study aims to determine the relationship between food consumption and obesity in adults between 40 and 55 years of age in the "Barrio Sur" sector of the Jujan Canton, Guayas Province. The following work presents a quantitative, inductive and cross-sectional project, which is defined through the calculation of the Body Mass Index in adults, through questions and observation data, aged between 40 and 55 years in the field of Primary care in the "Barrio Sur" sector of Jujan Canton, Guayas Province. Quantitative, through statistical analysis, through a questionnaire of online questions, such as frequency of consumption. Inductive, since they are obtained from hereditary data that the researcher intervenes and is limited to measuring the variables (height and weight). Cross-sectional, since it examines the relationship between the disease and a series of variables in a specific population and time. According to the results with 95% reliability, 61 adults from 40 to 55 years of age from the ''Barrio Sur'' Sector of the Jujan Canton, Guayas Province are indicated as a sample. The results showed that 52.4% of the sample is overweight, 36.1% has type I obesity, 8.2% has type III obesity and 3.3% has type II obesity. As a conclusion, there is only a relationship between the Body Mass Index with the consumption of sausages. In the other questions asked to identify food consumption, it was found that there is no relationship between these variables, the chi-square statistical test of the SPSS application was used.